The Governance of Artificial Intelligence in Line with the International Human Rights Law - Hilal, Ghofran M. I.; Chabaan يسرا محمد محمود; Njehi أمال محمد منور (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: This paper aims to analyze the governance of Artificial Intelligence (AI) from the Human Rights (HR) perspective. It started with identifying the relationship between AI and HR by evaluating the opportunities and risks that AI poses to HR. It also examined the adequacy of international human rights law rules for protecting individuals from these risks. Moreover, it provided a vision for the possibility of AI governance aligning with HR. Methods: The inductive-analytical approach was followed by examining the impact of AI on HR and analyzing the most important instruments related to HR protection while stating their role in regulating the governance of these technologies to preserve the human rights and dignity of individuals. Results: The paper reached several results, including that AI opens new horizons for the development of human civilization. However, it poses many social and legal risks to both individuals and States. We have also found that the general rules regulating HR stipulated in international instruments are insufficient to accommodate the development of AI technologies. Conclusions: The paper concluded that AI must be developed by adopting an approach based on consolidated ethical values and principles of respect for HR. Moreover, it also emphasized the importance of internationally unifying general principles or adopting guidelines to regulate AI under the umbrella of the United Nations. In formulating these guidelines, it is necessary to involve all relevant parties, such as governments, international organizations, and independent experts involved with AI.